The Impact of Digitalization on Traditional Markets: Transformation and Challenges in the Era of E-commerce - Indah, Syahnifa Nur; Rusdi, Muhammad; Pratiwi, Haslindah; Samiri, Muliani (Jurnal Studi Ilmu Pemerintahan, 2024)
This study examines the impact of digitalization on traditional markets, with a particular focus on understanding the transformations and challenges faced by these markets in the era of e-commerce. A quantitative approach was employed to collect data from conventional market vendors in Rappang City, which were then analyzed using simple linear regression and other statistical methods via SPSS 26. The findings indicate a notable and positive correlation between digitalization and the performance of traditional markets, with a regression coefficient of 0.771, suggesting that digitalization significantly enhances traditional markets' competitiveness and operational efficiency. Moreover, the study underscores that while digitalization offers a plethora of avenues for conventional markets to integrate with digital platforms and extend their reach, it also presents challenges, including intensified competition from e-commerce and the necessity for rapid adaptation to new technologies. The findings indicate that digitalization is not merely a supplementary tool but rather a critical component for sustaining the relevance and competitiveness of traditional markets in the modern digital economy. The study concludes that stakeholders in traditional markets must adopt strategic digitalization initiatives, supported by appropriate policies and infrastructure investments, to ensure these markets can thrive alongside emerging e-commerce platforms. Despite the study's regional focus, the implications extend to broader contexts, offering insights into how traditional markets globally can navigate the challenges posed by digital transformation. Future research should consider a mixed methods approach to explore the nuanced impacts of digitalization in different cultural and economic settings.